2020
DOI: 10.3390/ani10091586
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of New South Wales Sheep Producer Practices and Perceptions on Lamb Mortality and Ewe Supplementation

Abstract: High lamb mortality rates reduce profitability and reduce the perceived animal welfare standards of the industry. This study aimed to understand producer knowledge of lamb mortality rates and causes of lamb mortality, and to investigate various practices and perceptions of producers that may contribute to lamb deaths. Postal and online surveys gathered data on Australian sheep producer’s knowledge and practices around lambing and management practices. Based on results, approximately 50% of producers estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
3
10
0
1
Order By: Relevance
“…National lamb marking rates reported by Meat and Livestock Australia (2019) were 82% for Merinos and 108% for non-Merinos. The somewhat higher percentages reported by respondents in this study suggests that some producers may be overestimating lamb marking and lamb survival rates, which corresponds with conclusions found in other studies (Kubeil 2017;Munoz et al 2019;Kopp et al 2020). Lamb marking percentages reported by respondents are presented in Table 1.…”
Section: Production Characteristics and Demographicssupporting
confidence: 88%
“…National lamb marking rates reported by Meat and Livestock Australia (2019) were 82% for Merinos and 108% for non-Merinos. The somewhat higher percentages reported by respondents in this study suggests that some producers may be overestimating lamb marking and lamb survival rates, which corresponds with conclusions found in other studies (Kubeil 2017;Munoz et al 2019;Kopp et al 2020). Lamb marking percentages reported by respondents are presented in Table 1.…”
Section: Production Characteristics and Demographicssupporting
confidence: 88%
“…As the majority of the farmers in the current study lambed indoors and the ewes and their lambs were not turned out to pasture until a few days post partum, it is unlikely that predators would be the main cause of lamb mortality even though farmers believed they were. However, farmers tend to choose issues/factors that they have no control over (e.g., predators and weather) rather than those that they do (e.g., birth weight, disease), which is similar to a recent study in Australia where farmers overestimated predation at three times more likely to be the primary cause of mortality than the published data [ 35 ].…”
Section: Discussionsupporting
confidence: 55%
“…While lamb mortality is a key factor influencing ewe productivity, thus flock profitability, most farmers in this study did not record lamb mortality. A recent survey study in Australia of sheep farmers’ perceptions of lamb mortality reported that producers may be largely underestimating their mortality incidence compared to experimental studies of similar breeds and using similar management practices [ 35 ]. However, in the current study, when asked to provide the number of lambs that died on the farm, there was little difference in numbers between the farmers who recorded lamb mortality and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…El 70.59% de las muertes ocurrió durante las primeras 48 horas posteriores al parto siendo el síndrome de inanición exposición la principal causa de mortalidad general y pre-destete y la fotosensibilización hepatógena la principal causa de muerte post-destete (Tabla 1). Diversos estudios realizados en la misma región de estudio (Macedo et al, 2010) y en diversas partes del mundo (Tifashe et al, 2017;Kopp et al, 2020) coinciden en que el síndrome de inaniciónexposición representó la principal causa de muerte de los corderos. Llama la atención la ausencia de muertes ocasionadas por infecciones de diversos tipos, las cuales se documentan como la principal causa de muerte en estudios recientes (Murray et al, 2019;Mlimbe et al, 2020;Tesema et al, 2020).…”
Section: Resultados Y Discusiónunclassified